Response of Wolves to Corridor Restoration and Human Use Management - Shepherd, Brenda; Whittington, Jesse (Resilience Alliance, 2006)
Corridor restoration is increasingly being used to connect habitat in mountainous areas where rugged topography and increasing human activity fragment habitat. Wolves (Canis lupus) are a conservation priority because they avoid areas with high levels of human use and are ecologically important predators. We examined how corridor restoration through a golf course changes the distribution of wolves and their prey in Jasper National Park, Alberta, Canada. We followed and recorded wolf paths in the snow both within the corridor and in the surrounding landscape before and after a corridor was re-established. Track transects were used to estimate prey abundance and snow depths, and trail counters measured human activity. We compared resources on wolf paths to available movement routes using conditional logistic regression and also compared resources used by wolves before and after restoration. We addressed potential confounding effects of prey abundance, snow depths, and levels of human use by testing for changes in these variables. Prior to restoration, wolves traveled around the golf course and used the mountainside to connect valley-bottom habitat. Conversely, elk (Cervus elaphus) densities were highest in the golf course. After restoration, wolves shifted most of their movement to the golf course corridor, whereas elk dispersed along the corridor and mountainside. When traveling through the study area, wolves selected for areas with high prey abundance, low elevations, and low levels of human activity. Corridor restoration increased the area of high quality habitat available to wolves and increased their access to elk and deer at low elevations. Our results corroborate other studies suggesting that wolves and elk quickly adapt to landscape changes and that corridor restoration can improve habitat quality and reduce habitat fragmentation.